Sosialisasi ‘Ariyah dalam Islam Di Kecamatan Air Kumbang Kabupaten Banyuasin - Saprida Saprida; Choiriyah Choiriyah (AKM, 2020)
This community service activity discusses the introduction of ariyah or loans both from the definition of ariyah, the legal basis of ariyah, the pillars and conditions of ariyah, the types of ariyah, the responsibilities of the borrower, and the end of the ariyah contract. The purpose of this community service activity is to give an introduction about 'ariyah to recitation mothers in Nusa Makmur village with the aim of socialization participants to be able to know about the procedures for lending in Islamic law. Participants in socialization can also understand the importance of helping fellow human beings with help in helping kindness can bring the relationship of affection and love between Muslims. Giving loans to others in need is a rewarding worship, because it enters into the publicity of helping in goodness and piety